Assessment of the Environmental and Health risks of Chromium in the Soil of Tanning Factories (Baghdad City - Iraq) - Rawnaq Mahdi (Engineering and Technology Journal, 2023)
The present study assesses the pollution level and health risk of heavy metal (Cr) in the area surrounding the tanning factories’ soil in Baghdad city-Iraq. Chromium concentration, mean, and median values were calculated. The geoaccumulation index (Igeo), the enrichment factor (EF), and the integrated pollution index (IPI) have been used in the assessment of pollution. The lowest value of (Igeo) at the surface to the north of the factory was (2.36), and the highest value of (Igeo) at a depth of 100 cm from the surface to the south of the factory was (94.94). All values of (EF) were greater than 40. The values of (IPI) at the surface and a depth of 100 cm from the surface of the soil are considered to cause an extreme level of contamination. A depth of 50 cm from the surface of the soil to the north of the factory is considered to have a high level of contamination. In addition, the estimated health risk was assessed by calculating the values of hazard quotient (HQ), health index (HI) for non-carcinogenic, lifetime average daily dose (LADD) for carcinogenic heavy metals, and lifetime cancer risk (R). The values of HI were found at a safe level (<1).  Moreover, carcinogenic risks were estimated by the exposure results, where the highest value of R was 51.9, and the lowest value was 0.231.